2015
DOI: 10.3906/sag-1406-61
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality and sexual dysfunction in spinal cord-injured men in Turkey

Abstract: Background/aim: To provide a comprehensive evaluation of sexual function and dysfunction in spinal cord-injured men based on self-reports of patients.Materials and methods: Forty-seven spinal cord-injured men who completed the spinal shock and rehabilitation period were included.Patients were asked to complete a questionnaire developed to assess social status, sexual activities, abilities, and sexuality education after injury. Neurologic levels of patients were classified according to American Spinal Cord Inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 13 publications
2
11
0
5
Order By: Relevance
“…The physical changes caused by this condition impact on the life of people who have the trauma directly, including the aspect of sexual satisfaction, thus interfering with the psychological and social components as a consequence of an altered self-perception. (1,2) The worldwide incidence of spinal cord trauma is from 15 to 40 new cases per year per one million people. In Brazil, the estimated incidence is 40 new cases per year per one million people, with 80% of the victims being men and 60% between 10 and 30 years old.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical changes caused by this condition impact on the life of people who have the trauma directly, including the aspect of sexual satisfaction, thus interfering with the psychological and social components as a consequence of an altered self-perception. (1,2) The worldwide incidence of spinal cord trauma is from 15 to 40 new cases per year per one million people. In Brazil, the estimated incidence is 40 new cases per year per one million people, with 80% of the victims being men and 60% between 10 and 30 years old.…”
Section: Introductionmentioning
confidence: 99%
“…For tetraplegic patients, this worry is secondary, because regaining the motor function is their priority, given the greater impairment of motricity and mobility they suffer. (2,(4)(5)(6) Sexual satisfaction is an important aspect of the life of people with spinal cord injury, and different treatment methods for sexual dysfunctions and adaptations in sex life must be considered to improve the quality of life of these people. (6,7) Healthcare professionals have the responsibility to promote sex education of people with spinal cord injury to reduce the impact of the condition on sexuality and the sexual function and improve the quality of life of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…12 Akman reported that Turkish men with SCI preferred to have sexual education given by physicians after the completion of the rehabilitation period, yet in that study, only 8.5% of patients received sexual education after injury. 15 Though no consensus exists on the timing, methods and details of sexual education after traumatic SCI, we believe that a protocol for this aspect of management is warranted. Alexander made recommendations for discussing sexual health with patients with SCI by providing sensitive information and being available to answer questions.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study assessing the long-term outcome of erectile function in men with SCI, 61% of respondents reported having erections without pharmacological or assisted devices, however, in most patients the quality of erections was poor (turgor and duration). 14 Akman reported that in 47 Turkish men with a history of a SCI,~94% reported the presence of erections, however, 87% 15 Psychogenic and reflexogenic erections may be preserved in men with SCI, however, these erections are usually of poor quality and may not permit satisfactory intercourse. In fact, in our study, most men reported poor overall satisfaction with intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…Cuenca et al 19 estabeleceu uma relação entre a depressão, ansiedade, auto-estima com a disfunção sexual de homens com lesão medular. Já Akman et al 20 pontuam que a continuação da atividade sexual após a lesão é muito importante e tem um grande impacto na qualidade de vida e no relacionamento interpessoal de homens lesionados na medula espinhal e, por isso, mais atenção deve ser dada à sexualidade após lesão medular.…”
Section: Discussionunclassified